Critical Analysis of the Inclusive Education Implementation in the Concept of Freedom of the Soul and Zona Proximal Development - Wijiastuti, Asri; Masitoh, Siti; Ainin, Ima Kurrotun; Ardianingsih, Febrita (Jurusan Pendidikan Luar Biasa)
AbstractKi Hadjar Dewantara laid the foundation of education in Indonesia through his thoughts related to the nature of children in 1913-1919. On the other hand Lev Vygotsky (1896-1934) stated a theory that children are able to learn with the help of competent people. Both theories illustrate that the implementation of education will provide freedom and happiness for children in learning to learn by understanding children naturally and as they are. Research that has been done using ethnographic design aims to dissect and trace Ki Hadjar Dewantara's thoughts and Vygotsky's theory in the implementation of inclusive education. Data collection is done through documentation studies, guided group discussions, and questionnaires. The results of the analysis of the position of Vygotsky's theory in the implementation of inclusive education in the concept of the Zone of Proximal Development are focused on how children construct knowledge according to their culture and ways. The ZPD concept which focuses on cognitive theory emerged around 1993 which in Indonesia itself had been developed by Ki Hadjar Dewantara in 1913-1919 the emphasis was on teaching according to the nature of the child. Ki Hadjar's philosophy is heavily influenced by Maria Montessori's thoughts which emphasize the value of children's independent activities and the importance of children's growth as individuals. In 1952 Ki Hadjar Dewantara created a